Sponge–Microbe Interactions on Coral Reefs: Multiple Evolutionary Solutions to a Complex Environment - Freeman, Christopher J.; Easson, Cole G.; Fiore, Cara L.; Thacker, Robert W. (Frontiers in Marine Science, 2021)
Marine sponges have been successful in their expansion across diverse ecological niches around the globe. Pioneering work attributed this success to both a well-developed aquiferous system that allowed for efficient filter feeding on suspended organic matter and the presence of microbial symbionts that can supplement host heterotrophic feeding with photosynthate or dissolved organic carbon. We now know that sponge-microbe interactions are host-specific, highly nuanced, and provide diverse nutritional benefits to the host sponge. Despite these advances in the field, many current hypotheses pertaining to the evolution of these interactions are overly generalized; these over-simplifications limit our understanding of the evolutionary processes shaping these symbioses and how they contribute to the ecological success of sponges on modern coral reefs. To highlight the current state of knowledge in this field, we start with seminal papers and review how contemporary work using higher resolution techniques has both complemented and challenged their early hypotheses. We outline different schools of thought by discussing evidence of symbiont contribution to both host ecological divergence and convergence, nutritional specificity and plasticity, and allopatric and sympatric speciation. Based on this synthesis, we conclude that the evolutionary pressures shaping these interactions are complex, with influences from both external (nutrient limitation and competition) and internal (fitness trade-offs and evolutionary constraints) factors. We outline recent controversies pertaining to these evolutionary pressures and place our current understanding of these interactions into a broader ecological and evolutionary framework. Finally, we propose areas for future research that we believe will lead to important new developments in the field.